The European Health Data Space as a Case Study - Dove, Edward S (Ethics & human research, 2024)
In May 2022, the European Commission proposed the launch of a health-specific data sharing framework called the European Health Data Space (EHDS), underpinned by legislation, for the use of electronic health data by patients and for research, innovation, policy-making, patient safety, statistics, or regulatory purposes. In this essay, I review some of its more contentious features based on the latest version of the legislative proposal. I suggest that the EHDS is a useful case study to illustrate the need for a translational bioethics approach that shines a critical analytical light on contentious aspects of large-scale research infrastructures.